(untitled) (Research, Society and Development, 2023)
Osteogenesis imperfecta (OI) is a congenital and chronic atavistic disease that affects bones through their fragility, linked to the process of deterioration of bone connective tissue. The objective of the study was to systematize the production of knowledge about periodization and prescription for patients with OI, bringing exercise indications. The Portal Regional BVS, SciELO, PubMed, Cochrane and Research Gate databases were used for the search. With the eligibility criteria applied, 2 studies were selected, a randomized clinical trial and a systematic review. Work on reducing joint stress, gaining muscle strength, developing sensory-motor stimulation, biomechanical alignment and swimming are the most recommended recommendations regarding the axis of periodization and prescription in OI. Strength exercises, light load progressions, aerobics on a bicycle, whether stationary or not, are also recommended for this target audience. Studies in the scientific literature are still superficial when it comes to physical training, physical activity and physical exercise in patients with OI, requiring theoretical and scientific deepening. Periodization and prescription are based mostly on low-impact exercises, seeking to improve the patient’s well-being, however, strength exercises are also options in periodization, seeking to improve bone mineral density. There is a gap regarding periodization and prescription guidelines for patients with OI, in which the vast majority of exercises are associated with a physical therapy practice, requiring further update and intervention studies.